Stock indices breakdown during the pandemic as the most dynamic bear market in history: Consequences for individual investors - Piotr Dabrowski (Risks, 2021)
The breakdown of stock indices is an obvious part of the financial market cycle. A common question about a bear market is the time and the depth of the downtrend, as well as the speed of the following recovery. As the COVID-19 pandemic spread globally, it induced huge price drops in a very short period, and an uptrend with new historical highs afterwards. The results of this research show that the pandemic breakdown was the fastest bear market in history; however, it does not confirm that future downtrends will be at the same or even greater speed. The consequences for individual investors have forced them to prepare for possible similar market behavior in the future, and to adjust their trading techniques and strategies to these conditions
Keywords: 330; COVID-19; bear market; drawdown; recovery; capital markets; individual investor